Necessity and securing plan of airfield exclusive for test and evaluation infrastructure in military aviation fields - Sungkak Cho; Yongdae Kim (선진국방연구, 2023)
This study addresses the problem of the absence of an airfield dedicated to flight tests, particularly since the need for flight tests has increased significantly with the development of the domestic aviation industry. In particular, the development of unmanned aerial vehicles, including small drones, along with the development of manned aircraft such as KF-21 “Boramae,” marine attack helicopters, and mine-sweeping helicopters, continues to increase flight test requirements. However, developers are not able to secure sufficient flight test time owing to program schedules. Accordingly, industry/academic/research/military and programrelated institutions involved in aircraft development strongly hope to establish an airfield infrastructure dedicated to flight tests. However, to secure a new airfield, several problems must be addressed, such as civil complaints in the region and securing a large budget. Accordingly, this study analyzed various measures to secure a flight test airfield in the defense sector and proposed that a flight test airfield connected to a military airport relocation project could be the most reasonable alternative for resolving regional conflicts and securing budgets.